(Z)-7, 4′-Dimethoxy-6-hydroxy-aurone- 4-O-β-glucopyranoside alleviates cerebral ischemia-reperfusion injury in rats associating with the regulation of JAK1/STAT1 signaling pathway. (November 2020) - Du, R; Zhou, X; Yang, D; Zhou, H; Lin, F; Li, Q
Inflammatory responses have been demonstrated to contribute to the neuronal death following cerebral ischemia. This study was to investigate the repairing effects and potential mechanisms of (Z)-7, 4′-dimethoxy-6-hydroxy-aurone-4-O-β-glucopyranoside (DHAG), a compound with neuroprotective effects, on cerebral ischemia-reperfusion (I/R) injury in rats. Cerebral I/R model was established with middle cerebral artery occlusion method in Sprague Dawley rats and then rats were treated with DHAG (1 and 2 mg/kg) for 7 days. The volume of cerebral infarction was detected by triphenyltetrazolium chloride staining. The apoptosis in ischemic brain tissues was detected by terminal deoxynucleotidyl transferase dUTP nick end labeling assay. Oxidative stress markers and inflammatory factors were detected by enzyme-linked immunosorbent assay. Protein expression was detected by Western blot. DHAG treatment significantly alleviated the cerebral I/R injury and decreased apoptosis in brain tissues. Moreover, DHAG treatment significantly inhibited oxidative stress and reduced inflammatory responses, associating with decreasing the protein expression of phosphorylated Janus kinase 1/phosphorylated signal transducer and transcriptional activator 1. These results demonstrated neuroprotective properties of DHAG and highlighted it as a potential therapeutic agent against injury of cerebral IR.